Molecular characterization and phylogenetic relationships among and within species of Phalaenopsis (Epidendroideae: Orchidaceae) based on RAPD analysis - Niknejad, Azadeh; Abdul Kadir, Mihdzar; Kadzimin, Saleh; Abdullah, Nur Ashikin Psyquay; Sorkheh, Karim (Academic Journals, 2009)
Random amplified polymorphic DNA (RAPD) analysis for 20 species of Phalaenopsis was conducted to determine their genetic distances and relationships. Among 20 different primers used for RAPD analysis, 10 primers showed polymorphism, and according to the primer type, 26 to 54 DNA fragments were amplified. A total of 414 polymorphic fragments were generated by 10 primers and used for correlation group analysis. The highest value of Similarity index was 0.28 between Ph. violacea malaysia and Ph. violacea witte. The dendrogram resulting from UPGMA (Unweighted Pair Group Method using Arithmetic average) hierarchical cluster analysis separated the original species into three groups: The first group had five species of Ph. violacea blue, Ph. belina, Ph. violacea malaysia, Ph. violacea witte, and Ph. gigantea; the second group included Ph. lamelligera, Ph. amabilis, Ph. parishii, Ph. labbi nepal, Ph. speciosa, Ph. lobbi yellow, Ph. venosa, Ph. hieroglyphica, and Ph. maculata; the third group consisted of Ph. minho princess, Ph. leopard prince, Ph. mannii, Ph. modesta, Ph. cornucervi and Ph. pantherina. RAPD markers can thus be successfully applied in this economically important group of orchids for the study of molecular characterization and relationships. The data acquired from this study could be used for identification and classification of other orchid genera and oriental Phalaenopsis.